MR Microscopy of the Parotid Glands in Patients with Sjögren’s Syndrome: Quantitative MR Diagnostic Criteria - Takagi, Yukinori; Sumi, Misa; Sumi, Tadateru; Ichikawa, Yoko; Nakamura, Takashi (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: MR imaging of the salivary glands has been applied to the diagnosis of Sjögren’s syndrome; however, the diagnosis remains qualitative. We sought to establish and evaluate quantitative MR imaging criteria for the diagnosis of Sjögren’s syndrome.METHODS: MR imaging with a 47-mm microscopy coil was performed in 83 patients with xerostomia (55 patients with Sjögren’s syndrome, 28 without Sjögren’s syndrome). MR images were obtained by T1-weighted and fat-suppressed T2-weighted imaging and by MR sialography of the parotid glands. MR imaging findings of the parotid glands in Sjögren’s syndome included increases in fat areas and decreases in intact lobule areas. These MR images were morphometrically analyzed for the diagnostic criteria.RESULTS: MR imaging with a microscopy coil demonstrated well the details of the damaged parotid glands in patients with xerostomia. Quantitative MR imaging of fat, intact gland lobule, and number of sialoectatic foci significantly and highly correlated with severity of disease. Receiver operating characteristic (ROC) curve analysis demonstrated that quantitative MR imaging yielded high diagnostic ability in differentiating patients with xerostomia who have Sjögren’s syndrome from those without Sjögren’s syndrome, with areas under the ROC curve of 0.94 for fat area, 0.98 for intact lobule area, and 0.91 for number of sialoectatic foci. The best cutoff points by quantitative MR imaging were each associated with high sensitivity and specificity, and, when used in combination, yielded 96% sensitivity and 100% specificity.CONCLUSION: Quantitative MR imaging effectively differentiated the parotid glands in patients with xerostomia who have Sjögren’s syndrome from those without the syndrome and provided criteria for staging the gland disease.